Computational physics as a tool for understanding physics: a case study of quantum mechanics - Chancay Ortega, Hugo Kenneth (2024)
The simulation of different systems via computers introduces a new paradigm to study and comprehend physics. In particular, computational tools can help physicists and prospective physicists to focus on key concepts, by having the mathematical assistance of computer calculations. In the present thesis, the effects of applying this paradigm in a case study of quantum mechanics by simulating the theoretical model of the Markovian master equation for nonlinear systems is reported. The thinking process behind the simulation of the case study is reported with illustrations and an analysis that serves as a prelude of the advantages that the introduction of computational physics has to offer. It is shown the amount of information that can be obtained and how it may be treated. By doing this, physicists and prospective physicists will have another way of studying that might be able to improve their understanding of physics faster, in the case of the present thesis, their understanding of nonlinear open quantum systems.